2016
DOI: 10.1159/000452530
|View full text |Cite
|
Sign up to set email alerts
|

CD47 is a Potential Target for the Treatment of Laryngeal Squamous Cell Carcinoma

Abstract: Background/Aims: This study aims to investigate the effect of CD47 on the development of laryngeal squamous cell carcinoma (LSCC) and the therapeutic potential of monoclonal antibody against CD47 and its ligand SIRPα in the treatment of LSCC. Methods: We firstly detected the expressions of CD47 mRNA and protein in LSCC and para-carcinoma tissues, introduced the most efficient CD47siRNA sequence into LSCC cells by lentiviral transfection and employed three monoclonal antibodies to evaluate their anti-LSCC effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…IHC staining confirmed that CD47 was highly expressed in the tumor cells of patients with ESCC. These results are consistent with previously published data in which CD47 levels in tumor tissues were significantly higher than those in non-tumor tissues in patients with ESCC or LSCC (34,35). In addition, increased levels of tumor tissue infiltration by macrophages were observed in the current study.…”
Section: Discussionsupporting
confidence: 94%
“…IHC staining confirmed that CD47 was highly expressed in the tumor cells of patients with ESCC. These results are consistent with previously published data in which CD47 levels in tumor tissues were significantly higher than those in non-tumor tissues in patients with ESCC or LSCC (34,35). In addition, increased levels of tumor tissue infiltration by macrophages were observed in the current study.…”
Section: Discussionsupporting
confidence: 94%
“…Metabolism agents with anti-tumor effects, such as metformin, may decrease M2-like abundance and polarization (61). Inhibition of the interaction between CD47, a marker of self upregulated by tumor cells in the TME, and SIRPα, a surface molecule on TAMs, enhances phagocytosis and decreases the M2/M1 ratio (62). Humanized anti-CD40 antibodies have been shown to re-educate M2-like TAMs to become M1-like, and induce tumor regression and improve survival in pancreatic cancer mouse models and surgically incurable patients (63).…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal Abs, such as anti-SIRPα Abs, anti-CD47 BRIC126 Abs, and anti-CD47 B6H12 Abs, can promote macrophage phagocytic activity and inhibit tumor cell growth and metastasis. 20 CD47 was found to be a potential therapeutic target for diffuse malignant mesothelioma, and its binding to SIRPα on macrophages can inhibit phagocytosis. 21 Moreover, data on mouse research showed that CD47-CAR-T cells can kill cancer cells, such as ovarian cancer cells and digestive tumor cells.…”
Section: Evolutionmentioning
confidence: 99%
“…Monoclonal Abs, such as anti-SIRPα Abs, anti-CD47 BRIC126 Abs, and anti-CD47 B6H12 Abs, can promote macrophage phagocytic activity and inhibit tumor cell growth and metastasis. 20 …”
Section: Evolutionmentioning
confidence: 99%